PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PRODUK SUSU CAIR DALAM KEMASAN SIAP MINUM MEREK ULTRA MILK DI KOTA BANDUNG - Shalsa; Edi Nurtjahjadi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study to analyze the effect of product quality on repurchase intention mediated by customer satisfaction on liquid milk products in ready-to-drink packaging for the ultra milk brand in Bandung city.This researchused approach of quantitative.The research instrument has gone through the stages of validity, reliability testing, classic assumption test, simple regression test, and sobel test. There were 150 respondents who participated in this study. The analytical tool used to test the instrument data is using SPSS software version 24 and Sobel Test. The results showed that: 1) Product quality has a positive and significant effect on customer satisfaction, 2) product quality has a positive and significant affects on repurchase interest, 3) customer satisfaction quality has a positive and significant effect on repurchase interest, 4) product quality has a positive and significant effect on repurchase interest mediated by customer satisfaction.